Next-Gen Global Health 6.0: Integrative Genomics, Nano-Immunotherapies, and AI for Infectious and Chronic Disease Convergence - Dito Anurogo (International Journal of Health and Medicine, 2025)
The Next-Gen Global Health 6.0 initiative offers an integrative model employing genomics, nano-immunotherapies, and artificial intelligence (AI) to address the escalating complexity of global health issues, particularly the convergence of infectious and chronic diseases. This framework advances precision medicine by integrating real-time genomic surveillance with AI algorithms, enabling timely prediction and response to outbreaks, as well as tailored therapeutic approaches. Nano-immunotherapies play a critical role in modulating immune responses with high specificity, especially in chronic infections and diseases resistant to conventional treatments. Through these synergistic technologies, the Next-Gen Global Health 6.0 approach aims to transcend traditional healthcare boundaries, offering scalable, data-driven interventions that are adaptable to varying resource levels worldwide. Emphasizing accessibility and equity, this framework highlights the necessity for innovative health policies and interdisciplinary collaboration to optimize deployment in underserved regions, ultimately contributing to sustainable, resilient healthcare systems prepared for evolving global health challenges.